An Islamic approach to environment protection / Muhammad Dayyan and Rafia Afroz - Yusuf, Muhammad Dayyan; Afroz, Rafia (Faculty of Administrative Science and Policy Studies, 2012)
Environment is getting worst day by day especially in the Muslim countries. It urgently needs an effort to maintain or restore the quality of environmental whether through policy or behavior-individual approach. The characteristics of goods and services, consumption patterns, production techniques, treatment or disposal of residuals need to change in such a way can retain the environment degradation. The conventional approach whether Command-Control Approach and Market Approach profoundly concept that discuss to control and regulate the environment damage but it seem inadequate. The paper argues that Islam has a comprehensive manner on environmental protection. The Islamic approach integrates individual and government policies have granted stewardship to manage the earth in accordance with the purpose intended by his Creator. Individually Muslim imbued with faith (‘aqidah), worship (‘ibadah), and ethical (mu’amalah) have strong bearing for the environment protection. Institutionally, Islamic policy such as well-planning, legislation, monitoring, effectively address the problem of pollution in a wide variety of situations. It would promote environmental awareness and avoid all the causes of at the root of environmental problems.